PENGARUH KINERJA PENGURUS TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI KARYAWAN PT BANK RIAU KEPRI PEKANBARU - Anggriana, Debbie Anggriana Debbie; ', Suarman; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect on the performance board to participation member on a Koperasi Karyawan PT Bank Riau Kepri Pekanbaru (cooperative employee of PT Bank Riau Kepri Pekanbaru). Research method used is descriptive quantitative method. Population of 487 persons and 83 samples of members with proportionate stratified random sampling the population has no element of homogeneous and stratified proportionally as seen from the old to be a member. Data analysis techniques used by simple linear regression. From the result, it can be concluded that : the effect of the boardâ€™s performance against the members participation of the cooperative employee of PT Bank Riau Kepri Pekanbaru. Thus if you want to increase the participation of members it needs to be supported by an increase in the performance of the board. Key words : performance, participationÂ